Comorbidities and health-related quality of life among rural older community-dwellers in Vietnam - Hai Minh Vu; Hao Thi Tang; Vu Minh Hai (B); Cuong Duy Nguyen; My Ha Nguyen; Hanh Thi Kieu Le; Dat Cong Truong; Hien Xuan Luong (PLoS ONE, 2025)
This study explored the patterns of comorbidities and their impact on health-related quality of life (HRQoL) among elderly individuals living in rural communities in Vietnam. A cross-sectional study was conducted across four communes in Thai Binh province. The demographic characteristics and comorbidities of the participants were evaluated, along with their Euroqol-5 dimensions-5 levels (EQ-5D-5L), using a structured questionnaire supplemented by clinical examinations. A multivariate Tobit regression model was applied to assess the relationship between comorbidities and HRQoL. Results showed that a minority of participants (9.5%) were free of comorbidities. Cataracts were the most common condition (61.0%), followed by osteoarthritis (55.4%), rheumatoid arthritis (46.1%), and dementia (39.0%). The average EQ-5D index was 0.806 (SD =  0.184). Pain/discomfort, difficulties with usual activities, and anxiety/depression contributed most to the reduction in the EQ-5D-5L index. Participants with rheumatoid arthritis (β =  − 0.10; 95% CI =  − 0.13, − 0.07) and postural hypotension (β =  − 0.08; 95% CI =  − 0.14, − 0.02) experienced the greatest decrease in EQ-5D index, followed by those with urinary diseases (β =  − 0.05; 95% CI =  − 0.09, − 0.02) and stroke (β =  − 0.05; 95% CI =  − 0.09, − 0.01). This study highlights the high prevalence of comorbidities among the elderly in rural Vietnam, with arthritis, postural hypotension, urinary diseases, and stroke being most strongly associated with reduced HRQoL. Regular screening and monitoring of comorbidities are vital to identify individuals who would benefit most from healthcare interventions to enhance HRQoL.